Twist parameter Influence on Heat Transfer Coefficient Augmentation for a square Twisted Tube - Abdulkareem Abbas KhudhairAl-Musawi (Engineering and Technology Journal, 2013)
Heat transfer augmentation due to twisting parameter was investigated in atwisted tube of square cross sectional area. Twisting parameter is defined as the ratio of the length of the tube where it completed twisting of360 degrees to its hydraulic diameter.Four twist parameters were chosen;5, 10, 25 and 50, and a comparison is made with a straight untwisted duct.Two sets of Reynolds numbers were considered for laminar and transient flow. The laminar flow is performed at Re=500,1000,1500 and 2000. While for transient flow the range of Reynolds number are Re=5000,6000,7000,8000 and 9000.Theinfluence of twist parameter on convective heat transfer coefficient in laminar and transient flow was investigated.Numerical simulations were performed for three-dimensional, steady state incompressible flow in body-fitted coordinate using finite volume method and standard k-ε turbulence model. For the heat transfer problem the uniform wall temperature (UWT) boundary condition at tube wall is considered.It was observed that the heat transfer coefficient increases with decreasing twist parameter. This is interpreted to the nature of span wise swirling flow generated. The swirling increases cross flow velocity vectors as it becomes far from tube center towards walls. At tube wall the thickness of boundary layer becomes thinner as near wall velocity become larger which leads to a boundary layer of good thermal characteristics. Also swirling increases internal mixing process which enhances internal thermal equilibrium. The heat transfer coefficient also increases as Reynolds number increased as velocity components are increased